2019
DOI: 10.1021/acs.nanolett.9b01481
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Phosphorus Incorporation in Homoepitaxial P-Doped (111) Diamond Revealed by Photoelectron Holography

Abstract: Diamond has two crystallographically inequivalent sites in the unit cell. In doped diamond, dopant occupation in the two sites is expected to be equal. Nevertheless, preferential Supporting Information. I. Simulated photoelectron holograms for substitutional P, PVSVC, and interstitial P, and II. details of PEH technique (file type: PDF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…For the crystal structure analysis, we use white neutron holography, a kind of atomic resolution holography that can directly reveal a three-dimensional local structure around a dopant without any structure model. The white neutron holography exhibits higher sensitivity to light elements, such as hydrogen, B, and oxygen, compared with X-ray fluorescence holography and photoelectron holography. Thanks to the white neutron holography, we successfully revealed that the B-doping site in the Mg 2 Si SCs is the Mg site . Similarly, we determine the B-doping site in the Mg 2 Sn SCs using the white neutron holography.…”
Section: Introductionmentioning
confidence: 91%
“…For the crystal structure analysis, we use white neutron holography, a kind of atomic resolution holography that can directly reveal a three-dimensional local structure around a dopant without any structure model. The white neutron holography exhibits higher sensitivity to light elements, such as hydrogen, B, and oxygen, compared with X-ray fluorescence holography and photoelectron holography. Thanks to the white neutron holography, we successfully revealed that the B-doping site in the Mg 2 Si SCs is the Mg site . Similarly, we determine the B-doping site in the Mg 2 Sn SCs using the white neutron holography.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, we usually perform the DA30 angular mapping at different 2 and ' angles and then combine the maps analytically into a photoelectron hologram of a large solid angle (Matsushita et al, 2020). Some photoelectron holograms obtained by this method have already been reported (Tsutsui et al, 2017;Yokoya et al, 2019). In these reports, by taking advantage of the high photoemission intensity, photoelectron holograms of dopants in semiconductors were successfully observed for each chemically shifted core-level photoemission peak resolved by the high-energy-resolution DA30 analyzer.…”
Section: Figurementioning
confidence: 99%
“…Therefore, the atomic structures and chemical states of the active and inactive dopant sites could be clarified. By adopting the experimental PEH and the scattering pattern extraction algorithm that one of the authors developed (the maximum entropy method/L1 regularization (SPEA-MEM/SPEA-L1) method), it is possible to experimentally visualize the local 3D atomic structure around the dopant atoms. The schematic of this PEH is shown in Figure .…”
Section: Introductionmentioning
confidence: 99%